Hashemite University English Department graduate students' perspectives on Anglo-American literature and culture - Obeidat, & Shadi S. Neimneh, Kifah M. Al-Omari, Marwan M. (Opción, 1970)
This study complements another conducted earlier by the researchers, which examined undergraduate student responses in the same department. The findings of the previous study were published in an article entitled “Bridges or Walls? The article mainly focused on the pedagogical approach that attempts to find out the best practices for teaching courses on Anglo-American literature and culture in a given context stated above. After investigating the responses of a little more than forty graduate students, it was found out that (30) students, 75% of the whole group of students/respondents, have positive attitudes towards the teaching practices of the courses under investigation.